Transfusion-Related Acute Lung Injury (TRALI): A Narrative Literature Review - Hana Novera; Russilawati Russilawati; Dessy Mizarti (HM Publisher, 2023)
Transfusion-related acute lung injury (TRALI) is defined as the onset of respiratory distress in a patient after receiving a blood component transfusion. So far, TRALI is considered a rare complication in the field of blood transfusion. However, in the last decade, there has been a shift in perspective. Currently, the US Food and Drug Administration recognizes the syndrome as the leading cause of transfusion-related death. This literature review aims to describe TRALI and its prevention strategies. Understanding the pathogenesis of TRALI drives prevention strategies from a blood bank perspective. A major breakthrough in efforts to reduce the incidence of TRALI was excluding female donors from the high plasma volume product, which resulted in an approximately two-thirds reduction in incidence. However, this strategy has not completely eliminated complications of transfusion. In recent years, research has identified patient-associated risk factors for the development of TRALI and empowered clinicians to take an individualized approach to patients requiring transfusion.